An assessment of the variation of soil properties with landscape attributes in the highlands of Cameroon. Land Degradation and Development - Takoutsing, B.; Weber, J.; Martín, R.A.; Shepherd, Keith D.; Aynekulu, Ermias; Sila, Andrew M. (Wiley, 2018)
Soil properties are useful for assessing the potential of landscapes to provide terrestrial ecosystem services, but they are affected by anthropogenic activities and environmental factors including landscape attributes. This study assessed how soil properties are influenced by landscape attributes and their interactions in the highlands of Cameroon using the Land Degradation Surveillance Framework as a data collection tool. Soil properties (soil organic carbon [SOC], clay content, exchangeable bases [ExBas], electric conductivity [EC], boron [B], manganese [Mn], phosphorus [P], pH) were quantified within classes of landscape attributes. Soil samples were collected on 160 (1,000 m2) plots randomly located in a sentinel site of 100 km2 and were analyzed using a combination of conventional laboratory methods and mid‐infrared spectroscopy. Soil properties were highly affected by soil depths, land use types, slope gradients, and topographic positions, but less by their interactions. Significant interactions existed between land use types and topographic positions for SOC, EC, ExBas, and pH, and between slope gradients and topographic positions for pH, whereas Mn was influenced by the interaction between land use types and slope gradients. Most soil properties were higher in low altitude plots and those with higher vegetation cover but decreased in the upslope direction. The pH and clay contents were less affected by slope gradient confirming the inherent nature of the properties. These results are useful for site‐specific implementation of ecological intensification in areas with complex topography such as the highlands of Cameroon, offering a reference for future ecological policies and landscape restoration.